Practical data acquisition for instrumentation and control systems - Park, John.; Mackay, Steve (Oxford ; Boston : Elsevier, 2003)
* Covers all aspects of the data acquisition system from design and specification to programming, installation and configuration * Gives both the novice and experienced user a solid understanding of interfacing the PC and standalone instruments to real-world signals from the laboratory to the industrial plant * Provides a thorough grasp of PC data acquisition systems and the ability to design, specify, install and configure and program data acquisition systems quickly and effectively This book focuses on data acquisition and control using the PC and standalone instruments. The PC has made a dramatic impact in the ease with which the technician, scientist and engineer today can set up their own test and measurement system at a remarkably low cost. And this book aims to show you how easy it is with plenty of carefully researched information. The popular IEEE 488 interface is also covered. All aspects of the data acquisition system are included from design and specification to programming, installation and configuration. This book gives both the novice and experienced user a solid grasp of the principles and practical implementation of interfacing the PC and standalone instruments to real-world signals from the laboratory to the industrial plant. Once you have read the book, you will have a thorough grasp of PC data acquisition systems and will be able to design, specify, install and configure and program data acquisition systems quickly and effectively. * Covers all aspects of the data acquisition system from design and specification to programming, installation and configuration * Gives both the novice and experienced user a solid understanding of interfacing the PC and standalone instruments to real-world signals from the laboratory to the industrial plant * Provides a thorough grasp of PC data acquisition systems and the ability to design, specify, install and configure and program data acquisition systems quickly and effectively.
Introduction to Data Acquisition & Control; Analog and Digital Signals; Signal Conditioning; The Personal Computer for Real Time Work; Plug-in Data Acquisition Boards; Serial Data Communications; Distributed & Standalone Loggers/Controllers; IEEE 488 Standard; Ethernet & LAN Systems; The Universal Serial Bus (USB); Specific Techniques; The PCMCIA Card; Appendix A: Glossary; Appendix B: IBM PC Bus Specifications; Appendix C: Review of the Intel 8255 PPI Chip; Appendix D: Review of the Intel 8254 Timer-Counter Chip; Appendix E: Thermocouple Tables; Appendix F: Numbers Systems; Appendix G: GPIB (IEEE-488) Mnemonics & their Definition; Appendix H: Practical Laboratories & Demonstrations; Appendix I: Command Structure & Programming.
Includes index.
Keywords: Automatic data collection systems; Management information systems; Electronic books